Analisis Pengaruh Struktur Modal, Profitabilitas, Kebijakan Dividen, Tingkat Uang, Dan Kinerja Keuangan Terhadap Nilai Perusahaan Dalam Perspektif Akuntansi - Titin Nur Azizah; Hwihanus Hwihanus (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to analyze the influence of several factors that influence company value from an accounting perspective. The factors studied include capital structure, profitability, dividend policy, cash levels, and financial performance. This research was conducted to provide a deeper understanding of how these variables can influence company value. The research method used is a qualitative analysis method which is suitable for analyzing the relationship between variables. One source of data is taken from the company's annual financial reports over a certain time period. It is hoped that the results of this analysis will provide a clear picture of the extent of the influence of each variable on company value. The results of this research can be a guide for company management in making decisions regarding capital structure, dividend policy, and efforts to improve financial performance. In addition, the findings of this research can also provide insight to investors, financial analysts and regulators regarding the factors that need to be considered in assessing the health and value of a company. The conclusions of this research are expected to contribute to the accounting and finance literature by providing a better understanding of the relationship between capital structure, profitability, dividend policy, cash levels, financial performance, and firm value. This research can also be a basis for further research in exploring other factors that might also influence company value in an accounting context.